Numerical simulation of ship motion fully coupled with sloshing tanks by naoe-FOAM-SJTU solver. Issue 8 (7th October 2019) - Zhuang, Yuan; Wan, Decheng
Abstract : Purpose: The purpose of this paper is to verify the ability of our in-house solver naoe-FOAM-SJTU to solve the problem of exterior fluid field coupled with interior fluid field and discover the coupling effects between exterior field (ship motion) and interior field (sloshing tanks). Design/methodology/approach: The solving equation is based on Navier–Stokes equation, by comparing two turbulence models [laminar model and Reynolds-averaged Navier–Stocks (RANS)], of which RANS model are chosen to do the simulation. A unified approach is adopted to simulate exterior and interior fields simultaneously, keeping the pressure and velocity the same in external and internal fields. By adding a new function of calculating forces on different patches, the inner sloshing moments and external wave exciting moments can be output. Findings: The in-house solver naoe-FOAM-SJTU had the ability to simulate this problem and showed well agreement with experimental results. By considering ship motion with and without sloshing, it was figured that with the existence of sloshing tank, the ship natural frequency will be changed. When the two tank fillings are the same, there will be another roll peak appeared, which is natural frequency of sloshing tanks. Considering wave height and different filling influence, the nonlinearity of sloshing in tank may give non-proportional response to ship motion. Practical implications: With the ability to simulate well, the reality reference in the progress of FPSO or FLNG operation is obtained. Originality/value: The value of this paper is a fully coupled CFD method which is adopted to solve the coupling effects, showing the ability to do the work well. It gives a referenced detailed information of inner and outer fluid field. Meanwhile, it carried out the impact pressure and damping force around the ship, which indicates the practical information in operations.